Rancang Bangun Penampung Sampah Laut Portable (PSP) dan Uji Solar Panel untuk Mengurangi Sampah Laut - Amanda T Siboro; Feby Angelin Garizi Siahaan; Sarnaen Simanjuntak; Muhammad Zainuddin Zainuddin Lubis (JURNAL INTEGRASI, 2018)
Marine litter is waste created by human that has been discharged into the coastal or marine environment. Varied and widespread human activities can act as the source of marine litter. The sources may be located directly at sea, on the coast or inland. Litters can be transported over long distances and into marine habitat. Accumulation of marine litter can affects habitats, organism ecological function, and develops health problems. The objective of present study was to evaluate portable marine litter collector’s performance for eliminating marine litter. The methods consist of some steps i.e. measuring and comparing collected marine litter amount with the total daily average amount in the tested area which took place at Pantai Biru Sehati, Tanjung Piayu; identifying the size and type of material of the collected marine litter; measuring the scope that can be reached by the prototype; along with identifying oceanographic parameter regarding its effects on prototype performance. The results showed that the performance duration of the prototype on an optimum battery is 1 - 3 hours, 2800 rpm of motor speed, 1 - 4 kg of marine litter as the maximum weight that can be held by the prototype. Furthermore, the identified oceanographic parameters are speed current which was 0.7 m/s. The field test also indicates that the oceanographic parameter affects the prototype performance. Keywords : Design, marine litter, portable marine litter collector, oceanographic